2015
DOI: 10.1155/2015/706782
|View full text |Cite
|
Sign up to set email alerts
|

The Preventive Effect on Ethanol-Induced Gastric Lesions of the Medicinal PlantPlumeria rubra: Involvement of the Latex Proteins in the NO/cGMP/KATPSignaling Pathway

Abstract: Plumeria rubra (Apocynaceae) is frequently used in folk medicine for the treatment of gastrointestinal disorders, hepatitis, and tracheitis, among other infirmities. The aim of this study was to investigate the gastroprotective potential of a protein fraction isolated from the latex of Plumeria rubra (PrLP) against ethanol-induced gastric lesions and describe the underlying mechanisms. In a dose-dependent manner, the pretreatment with PrLP prevented ethanol-induced gastric lesions in mice after single intraven… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 48 publications
1
1
0
Order By: Relevance
“…There were some exfoliated cells appearing in the lumen, besides, intraepithelial lymphocytes and extra-vasated RBCs. These results were in accordance with some investigators [1,[27][28][29] , who reported that the ethanol had direct effect on gastric mucosa and had ability to induce necrosis of the surface gastric epithelial cells and also erosion. The presence of inflammatory cells infiltration and intra epithelial lymphocytes in gastric mucosa indicates ongoing inflammation.…”
Section: Discussionsupporting
confidence: 93%
“…There were some exfoliated cells appearing in the lumen, besides, intraepithelial lymphocytes and extra-vasated RBCs. These results were in accordance with some investigators [1,[27][28][29] , who reported that the ethanol had direct effect on gastric mucosa and had ability to induce necrosis of the surface gastric epithelial cells and also erosion. The presence of inflammatory cells infiltration and intra epithelial lymphocytes in gastric mucosa indicates ongoing inflammation.…”
Section: Discussionsupporting
confidence: 93%
“…In addition, they have confirmed the safety of the total alcoholic extract at up to 4000 mg/kg [ 39 ]. Ethanol gastric-inducedlesions are multifactorial and are linked to the reduction in the inherent stomach mucosa defensemechanism and that’s principally associated with the change in the microcirculation or maybe the oxidation stress [ 41 ]. To test for the possible cytoprotective activity of the purified ProLec, we initially performed a pilot study using a wide range of ProLec concentrations ranging from 0.25 mg to 1 mg/kg, excitingly all of these protein ranges showed, a dose-dependent, remarkable protective effect against ethanol-induced gastric lesion on experimental animals.…”
Section: Resultsmentioning
confidence: 99%